Quinoxalin-2-yl p-tolyl Ether - Hassan, N.D.; Tajuddin, Hairul Anuar; Abdullah, Z.; Ng, S.W. (International Union of Crystallography, 2008)
The dihedral angle between the two aromatic ring systems in the title compound, C(15)H(12)N(2)O, is 42.6 (1)degrees. The angle at the O atom is widened to 117.7 (1)degrees.